USE OF LH AND PROGESTERONE ASSAYS FOR OVULATION TIMING AND OPTIMIZING CONCEPTION IN BITCHES - SRIDEVI, P; VEERAPANDIAN, C (The Indian Journal of Animal Reproduction, 2011)
The most appropriate method for estimating the time of ovulation and fertile breeding time in bitches and itsrelationship with plasma progesterone and LH concentrations were studied in 20 sub fertile bitches. The LH surgeoccurred on an average 9.95 ± 0.67 days from day 1 of proestrual bleeding and the calculated time ofovulation ( LHsurge + 48. 00 hrs.) was 11. 95 ± 0 .67 days from the onset of proestru a I bleeding and ranged from 9 to 2 0 of thecycle. Quantitative estimation of progesterone showed that the levels tend to increase just prior to LH surge uptothe time if ovulation and the respective levels were 1 and 5 ng/ml. Progesterone levels of> 1 Ong/ml marked theonset offertile period. The qualitative progesterone assay kit was able to detect progesterone levels of 1 0 ng/ml in 100, 80 and 100 per cent of the samples accurately and hence could be used for detecting thefertile period.
Keywords: Ovulation; LH surge; Progesterone Assay; Bitches